Discrepancies between human and murine model cerebral aneurysms at single-cell resolution - Ji, Hang; Kuang, Guicheng; Yang, Hailan; Liu, Haitao; Li, Yue; Hu, Shaoshan; Xiao, Anqi; You, Chao; Sun, Haogeng; Fan, Chaofeng; Sun, Guozhang (Frontiers in Cell and Developmental Biology, 2025)
BackgroundThe murine model of cerebral aneurysm (CA) serves as a prevalent tool for investigating the molecular underpinnings of CA. However, the extent to which the CA murine model aligns with that of human remains elusive.MethodsThe present study employed a comprehensive integration and exploration of the single-cell RNA-seq (scRNA-seq) datasets, along with multiple trajectory and gene regulatory network analyses, to investigate the cellular and molecular discrepancies between human and murine model CAs.ResultsThe uniform manifold approximation and projection (umap) embedding exhibits that the primary discrepancies between human and murine model CAs reside in the cells of modifiable phenotype, encompassing vascular smooth muscle cell (vSMC), monocyte/macrophage, and neutrophil. The vSMCs from human CA tissue exhibit a fibroblast-like phenotype in comparison to that of murine model. Distinct patterns of neutrophil recruitment are observed in human and murine models, with the former characterized by neutrophil-derived CXCL8 and the latter by monocyte/macrophage-derived CCLs. In addition, macrophages originated from human unruptured CA express higher levels of M2 gene markers. Moreover, the inflammatory status of the CA tissue differs between humans and mouse models, with the former exhibiting a more acute and intense inflammation.ConclusionThese findings demonstrate subtle but important disparities between human and murine model CAs, and may shed light upon an optimization of murine CA model.